2017
DOI: 10.3390/molecules22101785
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Siegesbeckia orientalis Extracts on Advanced Glycation End Product Formation and Key Enzymes Related to Metabolic Syndrome

Abstract: Metabolic syndrome typically includes Type 2 diabetes associated with hyperglycemia, central obesity, dyslipidemia and hypertension. It is highly related to oxidative stress, formation of advanced glycated end products (AGEs) and key enzymes, such as carbohydrate digesting enzymes like pancreatic α-amylase and intestinal α-glucosidase, pancreatic lipase and angiotensin I-converting enzyme (ACE). This study used an in vitro approach to assess the potential of four extracts of Siegesbeckia orientalis linne on ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 73 publications
0
13
0
2
Order By: Relevance
“…Auto-oxidation of glucose in hyperglycemic state can lead to lipid peroxidation, altered antioxidant defense mechanisms leading to further dysfunctions in glucose metabolism and are known to be mediated by reactive oxygen species (ROS) (Chaudhry et al, 2016). In vitro antioxidant and anti-glycation activities of Siegesbeckia orientalis has recently been reported (Hung et al, 2017). Moreover, flavonoids have been shown to produce their antidiabetic effects through enhancement of insulin secretion via regeneration of pancreatic β-cells, enhancement of insulin mediated glucose uptake by target cells, inhibition of aldose reductase and increased uptake of Ca 2+ respectively (Marella, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Auto-oxidation of glucose in hyperglycemic state can lead to lipid peroxidation, altered antioxidant defense mechanisms leading to further dysfunctions in glucose metabolism and are known to be mediated by reactive oxygen species (ROS) (Chaudhry et al, 2016). In vitro antioxidant and anti-glycation activities of Siegesbeckia orientalis has recently been reported (Hung et al, 2017). Moreover, flavonoids have been shown to produce their antidiabetic effects through enhancement of insulin secretion via regeneration of pancreatic β-cells, enhancement of insulin mediated glucose uptake by target cells, inhibition of aldose reductase and increased uptake of Ca 2+ respectively (Marella, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome, a cluster of some metabolic disorder, including insulin resistance, dyslipidemia, hyperglycemia and hypertension (Huang, 2009). It is suggested that metabolic syndrome is an early pathological features of chronic disease like type 2 diabetes, which is characterized by increase of glucose levels following food intake (Hung et al, 2017). The inhibitory effects on key enzymes related to carbohydrate hydrolyzes, which located in the small intestine, were thought to be an effective strategy to control the condition of postprandial hyperglycemia (Subramanian, Asmawi, & Sadikun, 2008;Tucci, Boyland, & Halford, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sophie et al 20 found increased P4 metabolism in omental adipose tissue of women characterized by abdominal obesity, and they also found that P4 has an inverse association with WC in men. 21 As a critical contributor of MetS, 22 if there is a strong association between obesity and P4, we can infer that there is also an association between MetS and P4. Consistent with the present study, the results of their studies may speculate that the positive relationship between P4 and MetS in women.…”
Section: Discussionmentioning
confidence: 99%